PERUSAHAAN “ANTARA PRAKTEK BISNIS DAN PRAKTEK SOSIAL” (Studi Penerapan Corporate Social Responsibility di Indonesia) - Nuryadi Kadir (Fakultas Dakwah dan Komunikasi, 2015)
Companies are no longer seen as economic actors who are only concerned itself with the purpose of profit (profit) only in their business activities. Participation and social care company into an integrated strategy on economic and social practice, specialized in lifting the value and image of the company. Problems that occur between companies and communities in the Indonesian context is the conflict of ownership disputes over resource use, such as land conflicts. Corporate Social Responsibility is a commitment of the company or the business world to contribute to the sustainable economic development that is basically how to create a climate of ethical business practices. In realizing the people's welfare, required participation by all elements, including government, private (companies) and the community itself. As stated in the Limited Liability Company Act which requires the private sector to establish good relationships with stakeholders. CSR, community conditions will experience enhancing the quality of life, teranganinya social problems that become life-threatening. Furthermore, the quality of the environment remains the case, because of corporate governance by pushing the level of pollution resulting from the operation of the company.